Inverted Yoga and Near Syncope: An Unusual Diagnosis of Right Ventricular Myxoma - Wadie David; Narmeen Rehman; Robby Singh; Shukri David (Case Reports in Cardiology)
Primary cardiac tumors are extremely rare and are difficult to diagnose. Although usually benign in nature, myxomas require surgical resection due to their increased risk of embolic and cardiac complications, with the timing of resection dependent on the presentation and size of the tumor. However, if diagnosed early, patients with primary benign cardiac tumors have excellent prognosis following surgery. Therefore, a high index of suspicion and a wide differential diagnosis are very important in detecting rare conditions that can affect otherwise healthy individuals. We present an uncommon case of a right ventricular myxoma that was discovered when the patient was performing inverted yoga and experienced a near syncopal episode. Patient subsequently underwent an echocardiographic evaluation and was found to have a right ventricular myxoma that was excised. Although recurrence is rare, it is important for physicians to remain vigilant and continue careful and consistent follow-up for patients with a history of a cardiac myxoma.